1986
DOI: 10.1109/jsac.1986.1146466
|View full text |Cite
|
Sign up to set email alerts
|

Design Issues in the ISDN U-Interface Transceiver

Abstract: Abstract-The design challenges faced in the integrated circuit realization of the basic customer access U-interface transceiver at 144 kbits/s in the integrated services digital network (ISDN) are summarized. Given the cost and performance objectives, thisrepresents a very challenging design problem from an algorithmic and technology point of view. This survey paper describes the alternative design approaches concentrating on algorithmic issues as opposed to circuit design issues, in the context of the echo ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Empirical studies indicate that crosstalk is likely to be the limiting impairment on two-way transmission at the ISDN frequencies of interest. It has been shown that the crosstalk phenomenon can be accurately modeled using only two terms, namely the near-end crosstalk (NEXT) and the far-end crosstalk (FEXT) [8]. The NEXT and FEXT terms are identified in Fig.…”
Section: Adsl Line Impairmentsmentioning
confidence: 99%
“…Empirical studies indicate that crosstalk is likely to be the limiting impairment on two-way transmission at the ISDN frequencies of interest. It has been shown that the crosstalk phenomenon can be accurately modeled using only two terms, namely the near-end crosstalk (NEXT) and the far-end crosstalk (FEXT) [8]. The NEXT and FEXT terms are identified in Fig.…”
Section: Adsl Line Impairmentsmentioning
confidence: 99%
“…As an example, let us consider the conventional "linear interpolation" method in the time-domain. The term has a power series expansion which, if truncated to the first two terms, gives (10) Then, taking an inverse Fourier transform we get (11) a formula for the linear interpolation in the time-domain. The above result indicates clearly the limitations of the linear interpolator [12].…”
Section: Phase Correction In Frequency-domain (Dft)mentioning
confidence: 99%
“…The timing jitter can also be reduced by line coding. The self-equalizing line codes, such as Biphase and Wal-2 [31], reduce the duration of the impulse response significantly at the line output, and therefore are an example of preequalization.…”
Section: Equalization Techniquesmentioning
confidence: 99%